Contribution à l'évaluation des sites web des Centres Régionaux de Formation Professionnelle en Grèce - DIMITRIS K. VERGIDIS; ANASTASIOS TZINTZIDIS (Metaichmio Publications, 2013)
Regional Training Centres (RTC) has their own website which can be used by trainers and trainees. In this study, we present the website content of the RTCs, the opinions of the trainees of the sample and the trainers, as well as their proposals for the improvement of the website of the RTCs. We realized that the number of the trainees of the sample using the website of the RTCs was limited and their degree of satisfaction concerning the website was below average. The trainers declared moderate satisfaction from the website of the RTC where they worked, however only a few made proposals for its improvement.